Compact and High Performance Dual-band Bandpass Filter Using Resonator-embedded Scheme for WLANs - B. F. Zong; G. M. Wang; H. Y. Zeng; Y. W. Wang (Radioengineering, 2012)
A compact microstrip dual-band bandpass filter (DBBPF) with high selectivity and good suppression for wireless local area networks (WLANs) is proposed utilizing a novel embedded scheme resonator. Two passbands are produced by a pair of embedded half-wavelength mean¬dered stepped-impedance resonator (MSIR) and a quad-wavelength short stub loaded stepped-impedance resona¬tor (SIR) separately. The resonator is fed by folded T-shaped capacitive source-load coupling microstrip feed line, and four transmission zeros are obtained at both sides of the bands to improve selectivity and suppression. Simul¬taneously, the size of the filter is extermely compact be¬cause embedding half-wavelength MSIR only changes the interior configuration of quad-wavelength SIR. To validate the design method, the designed filter is fabricated and measured. Both simulated and measured results indicate that good transmission property has been achieved.